1970
DOI: 10.1063/1.1659379
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thin Surface Layers by Fe-57 Mössbauer Backscattering Spectrometry

Abstract: Fe-57 Mössbauer spectra for extremely thin surface layers (600–3000 Å) were obtained by detecting internal conversion electrons emitted after resonant absorption. The sample was placed inside a proportional counter specifically designed for Mössbauer backscattering measurements. Helium-10% methane flowgas was used to detect the conversion electrons. It is estimated from the observed spectra that this technique can be used to obtain Mössbauer backscattering spectra for iron-containing surface layers 50–3000-Å t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(23 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…This means that about 60% of the electrons emitted from the sample surface have originated within this layer. However, already in one of the first works on CEMS [5] it was shown that some resonant absorption could be seen even from 300 nm depth.…”
Section: Methodsmentioning
confidence: 94%
“…This means that about 60% of the electrons emitted from the sample surface have originated within this layer. However, already in one of the first works on CEMS [5] it was shown that some resonant absorption could be seen even from 300 nm depth.…”
Section: Methodsmentioning
confidence: 94%
“…Conversion electron Mössbauer spectroscopy (CEMS) was demonstrated already in 1970 [14]. Since that time observation of layers, thin layers and single atomic layers Fig.…”
Section: Cems-polarimetric Methodsmentioning
confidence: 99%
“…Conversion electron Mössbauer spectroscopy (CEMS) was demonstrated already in 1970 [14]. Since that time observation of layers, thin layers and single atomic layers In standard CEMS detectors, sample surface is perpendicular to the direction of gamma rays.…”
Section: Cems-polarimetric Methodsmentioning
confidence: 99%